Theoretical and Empirical Comparison of Electrical Properties of Porous Silicon - AL-Kadumi, Ahmed Kh.; Alwan, Alwan M.; Al-Batat, Ali H. (Science Journal of University of Zakho, 2013)
The present work is the study of the dark current density for porous silicon which is prepared by photo-electrochemical etching for n-type silicon by using laser power density of (10mw/cm2)and wavelength(650nm) under different anodization time(50,60)minute. ,The results obtained from this study shows different characteristics that of porous for the different porous Silicon layers. The empirical data of J-V characteristics are compared by using mathematical(a Poole-Frenkel-like, Schottky diode) models prepared the with assistance of Matlab program.